2022
DOI: 10.3390/ijms23147806
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide and Sphingosine-1-Phosphate in Neurodegenerative Disorders and Their Potential Involvement in Therapy

Abstract: Neurodegenerative disorders (ND) are progressive diseases of the nervous system, often without resolutive therapy. They are characterized by a progressive impairment and loss of specific brain regions and neuronal populations. Cellular and animal model studies have identified several molecular mechanisms that play an important role in the pathogenesis of ND. Among them are alterations of lipids, in particular sphingolipids, that play a crucial role in neurodegeneration. Overall, during ND, ceramide-dependent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 154 publications
(221 reference statements)
0
3
0
Order By: Relevance
“…Of the protective agents investigated in MS models, citicoline best matches the fit of cuprizone. Sphingolipids have a role in the development of neurodegenerative diseases via the promotion of ceramide-induced apoptosis [24]. Fingolimod, a sphingosine-1-phosphate receptor modulator, shares template fitting-points with its analogue sphingosine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the protective agents investigated in MS models, citicoline best matches the fit of cuprizone. Sphingolipids have a role in the development of neurodegenerative diseases via the promotion of ceramide-induced apoptosis [24]. Fingolimod, a sphingosine-1-phosphate receptor modulator, shares template fitting-points with its analogue sphingosine.…”
Section: Discussionmentioning
confidence: 99%
“…The research literature identifies many apoptosis-modulating compounds rele-vant to neuron degeneration in Parkinson's, motor neurone disease (MND), demyelinating diseases and the peripheral neuropathy of diabetes. Apoptosis and disease-inducing compounds investigated in animal models and cell culture: palmitic acid [3], dexamethasone [5], ceramide [24], glucose [25], tolbutamide [25],…”
Section: Compound Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they have been shown to modulate several viral processes (e.g., inflammation and infection), including those related to SARS-CoV-2. In this context, Cer and S1P play opposite roles since Cer mainly controls cell growth arrest, death, and senescence, whereas S1P regulates cell proliferation and survival [41]. Indeed, researchers demonstrated that the infection of cultured epithelial cells with the SARS-CoV-2 S protein activated the ASM, thus catalyzing the conversion of SMs into Cers [42].…”
Section: Sphingolipids In Sars-cov-2 Life Cyclementioning
confidence: 99%
“…Sphingolipids are one of the major lipid components of cell membranes and are involved in various physiological functions, such as the nervous, immune, and cardiovascular systems [6][7][8][9]. The sphingolipid metabolites ceramide, ceramide-1-phosphate (C1P), sphingosine, and sphingosine-1-phosphate (S1P) have been well studied in terms of regulating stress tolerance, proliferation, differentiation, and maturation in nervous system cells [10][11][12]. Therefore, it has been reported that sphingolipids are significantly involved in the pathogenesis of neurodegenerative diseases such as Parkinson's disease, Alzheimer's disease, and multiple sclerosis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%